(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Congenital heart defects are a group of diseases united by the presence of anatomical defects of the heart, its valvular apparatus or vessels that occurred in the prenatal period, leading to changes in intracardiac and systemic hemodynamics. The manifestations of congenital heart disease depend on its type; the most characteristic symptoms include pallor or cyanosis of the skin, heart murmurs, lag in physical development, signs of respiratory and heart failure. If a congenital heart defect is suspected, an ECG, FCG, radiography, EchoCG, cardiac catheterization and aortography, cardiography, MRI of the heart, etc. are performed. Most often, with congenital heart defects, cardiac surgery is resorted to – surgical correction of the detected anomaly.